GAMBARAN PERILAKU SELF HARM PADA REMAJA - Fenty Zahara Nasution; Selly Angraini (Jurnal Rumpun Ilmu Kesehatan, 2021)
This research is to find out how self-harm is formed in adolescents and what causes adolescents to do self-harm. This research is a qualitative descriptive approach using a quisiner observation method and a phenomenological study, namely a research strategy where researchers identify human experiences regarding a particular phenomenon. According to the study of phenomenology, it allows researchers to apply and apply their informant and interpersonal skills in conducting research. The data collection technique used in this study was using the SSCT test, SHI Questionnaire (self Harm Inventory), observation, closed interviews via WhatsApp. Self-harm is self-harm behavior defined as a person's behavior to injure oneself in various ways regardless of whether or not there is an intention and desire to die in adolescence. 19 years old who have done self-harm behavior Since the age of 16 years, then the 18-year-old A.A woman has done self-harm since high school at the age of 15 years. . The results showed that the form of self-harm behavior carried out by these teenagers showed behavior of crying in the middle of the night, blaming themselves, feeling empty, scratching, slashing on the surface of the skin, taking drugs randomly of any brand, drinking shampoo, speeding. speeding with a motorbike on the highway likes bloody pictures with a sense of relief, listening to music at a loud volume using the handset until the ears hurt. Factors that cause adolescents to carry out self-harm behavior are disappointment in parents, fear of emotional fathers, disappointment in mothers who do not pay attention, stress when bullied at school to depression caused by lack of ability to control negative emotions that are buried in individuals because some of the problems that occur in adolescents such as the lack of harmony and warmth in family relationships, problems with peers, and bullying.